Anticancer Activity of Murine Leukemia P-388 Cells and ADMET Analysis of Bioactive Compounds of Lawang Wood Methanol Extract: Study In Silico - Sinaga, Jonathan Cavin Ezra; Bisma, Hartanto; Katja, Dewa Gede; Momuat, Lidya Irma; Runtuwene, Max Revolta John (Jurnal Ilmiah Sains, 2025)
Lawang wood (Cinnamomum culilaban L. Presl.) is often used by the public as a traditional medicine. It has been studied to have inhibitory activity on one type of murine leukemia cell protein P-388, namely cyclin-dependent kinase 2, this protein is important in the process of blood cell malignancy. This research aims to determine the potential of the bioactive compounds contained in lawang wood in inhibiting the action of the cyclin-ependent kinase 2 protein (PDB ID: 5D1J) by molecular docking as well as evaluating the physicochemical and pharmacokinetic properties of lawang wood bioactive compounds. lawang wood bioactive compounds were extracted using methanol solvent and identified using Gas Chromatography-Mass Spectrometer (GC-MS). Molecular docking was carried out using PyRx software by docking at the active site of the cyclin-ependent kinase 2 protein receptor followed by Lipinski's rule of five testing, and ADMET screening using SwissADME and admetSAR. The GC-MS results of lawang wood methanol extract contained 9 bioactive compound components. The molecular docking results were compared with the molecular docking results of the native ligand which was used as a control in this study. Based on the results obtained, the compound 4-Phenylpyrazolidine-3,5-dione has the lowest binding affinity value (-7,7 kcal/mol). The five best compounds, namely 4-Phenylpyrazolidine-3,5-dione, 2H-1-Benzopyran-2-one, 5,7-dimethoxy-, 2H-1-Benzopyran-2-one, 4,7-dimethoxy-, Camphore, and Safrole fulfilled Lipinski's rules and showed good results in ADMET analysis. Keywords: Cinnamomum culilaban L Presl.; mololecular docking; cyclin-dependent kinase 2; ADMET predictions